Answer:
A. -25/27
Explanation:
Given:
The equation is given as:
![x^2+y^2=25](https://img.qammunity.org/2021/formulas/mathematics/high-school/vnmxwz0o1sr5tf74xy66w98qeib7mmg5i3.png)
To find:
at (4, 3)
Differentiating the above equation with respect to 'x', we get:
![(d)/(dx)(x^2+y^2)=(d)/(dx)(25)\\\\2x+2yy'=0\\\\x+yy'=0\\\\yy'=-x\\\\y'=(-x)/(y)------- (1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/31lxmihfe5jf4cwp7k6a0zevmw0t7nqwu5.png)
Value of
at (4,3) is given as:
![y'_((4,3))=-(4)/(3)-------- (2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hbhth4pwbivqiqfc8dq6grf753fcpztq4a.png)
Now, differentiating equation (1) with respect to 'x' again, we get:
![y''=(d)/(dx)((-x)/(y))\\\\y''=(y(-1)-(-x)y')/(y^2)\\\\y''=(-y+xy')/(y^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/k6r2hlkvx65kc5kyc830ejefncot33qros.png)
Now, value of
at (4,3) is given as by plugging 4 for 'x', 3 for 'y' and
for
![y'](https://img.qammunity.org/2021/formulas/mathematics/high-school/753pguxhdr0tclf7z5vsoxixllrarqkcxg.png)
![y''_((4,3))=(-3+(4)(-(4)/(3)))/(3^2)\\\\y''_((4,3))=(-3-(16)/(3))/(9)\\\\y''_((4,3))=(-9-16)/(3)/ 9\\\\y''_((4,3))=(-25)/(3)/ 9\\\\y''_((4,3))=(-25)/(3)* (1)/(9)\\\\y''_((4,3))=-(25)/(27)](https://img.qammunity.org/2021/formulas/mathematics/high-school/91k264c7whl5fryv7ojcy338jvd8a6aulz.png)
Therefore, the value of the second derivative at (4, 3) is option (A) which is equal to -25/27.